Boston On Track: Storytelling and ROI for community colleges. Issue 12 (16th February 2021) - Zizzo, Anne
Abstract : More than ever before, higher education institutions are operating in an incredibly competitive environment, and community colleges need to be forward‐thinking and innovative. These days, effective higher education marketing campaigns are story‐rich and measurable across all aspects of the institution: advancement, community partnerships, employee recruitment, athletics, alumni relations, research, and innovation — not just enrollment. Covering such a diverse need is difficult to do, especially as marketing budgets tighten and the demand for student financial aid and scholarships continues to climb.